Teachers’ Work Motivation in Schools under the Sa Kaeo Primary Educational Service Area Office 1 - ธุระตา, ทักษิณ; ชวศิริกุลฑล, นันทนา; รักษนคร, กุลจิรา (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This study aimed to examine, compare, and propose guidelines for enhancing teachers’ work motivation classified by gender, age, educational level, and school size. The sample consisted of 319 teachers under the Sa Kaeo Primary Educational Service Area Office 1 in the 2025 academic year, and interviewed group leaders and school administrators altogether of 5 people and five administrators were interviewed. The instruments included a five-point rating scale questionnaire (reliability = .97) and a semi-structured interview. Data were analyzed using descriptive statistics, t-test, one-way ANOVA, Scheffé’s post hoc test, and content analysis.           The research results were as follows; 1. The teachers’ work motivation in educational institutions, both overall and by individual aspects, was found to be at a high level. 2. The comparison of teachers’ work motivation classified by gender and school size revealed no statistically significant differences overall. However, when classified by educational level, a statistically significant difference was found at the .05 level. Likewise, when classified by years of work experience, a statistically significant difference was found at the .05 level. Therefore, pairwise comparisons were conducted using the Scheffé method. 3. The guidelines emphasized participative management, adequate resource support, and fairness in administration to enhance teacher motivation and promote sustainable school development.